M27 Effect of pirfenidone on breathlessness as measured by the ucsd-sobq score in patients with idiopathic pulmonary fibrosis (ipf) with moderate lung function impairment. (15th November 2017) - Glassberg, MK; Wijsenbeek, M; Gilberg, F; Petzinger, U; Kirchgaessler, KU; Albera, C
Abstract : Introduction: Treatment of IPF with pirfenidone slows disease progression as measured by changes in forced vital capacity (FVC), independent of baseline FVC values. In a previous analysis of patients with limited vs more advanced lung function impairment, increases in University of California, San Diego Shortness of Breath Questionnaire (UCSD-SOBQ) scores were more pronounced in patients with Gender Age Physiology index (GAP) stage II/III vs GAP stage I and in patients with baseline FVC <80% vs FVC ≥80%0 .1  We examined the effect of pirfenidone on UCSD-SOBQ in these subpopulations. Methods: 1247 patients in ASCEND (NCT01366209 ) and CAPACITY (NCT00287716 ; NCT00287729 ) were randomised to pirfenidone 2403 mg/d or placebo. Patients were stratified by GAP stage I vs stage II/III and by baseline%–predicted FVC. The effect of pirfenidone on UCSD-SOBQ score was assessed by continuous and categorical changes from baseline over 12 months, and by multiples of the minimal clinically important difference of 5 points for UCSD-SOBQ. Results: Pirfenidone-treated patients with GAP stage II/III had higher UCSD-SOBQ scores after 12 months than those with GAP stage I (median increase from baseline: 9.4 vs 5.0); similar Results occurred with placebo (12.5 vs 4.3). GAP stage II/III patients treated with pirfenidone had less increase in median UCSD–SOBQ score at 12 months compared with those receiving placebo (9.4 vs 12.5; median difference −3.5, 95% CI −6.2, –0.5; p=0.0161) with the curves diverging after 3 months (figure 1). Evaluation of categorical change for patients with GAP stage II/III demonstrated that pirfenidone reduced the proportion of patients with UCSD-SOBQ score increases of ≥15 points (45.6% vs 38.4%; p=0.0449) and ≥20 points (37.7% vs 28.6%; p=0.0089) at 12 months compared with placebo; increases of ≥5 or≥10 points were similar between treatment groups. Results in patients with%FVC ≤80% were comparable to GAP stage II/III. Conclusions: In patients with IPF with moderate lung function impairment, pirfenidone reduced the progression of breathlessness compared with placebo. Patients receiving pirfenidone showed less change from baseline in UCSD-SOBQ score and a lower proportion of patients had more pronounced increases in UCSD-SOBQ scores at 12 months. Reference: . Albera C et al. Eur Respir J2016;48:843–851.